DETERMINATION OF CORROSION INITIATION OF REBAR IN CONCRETE BY MONITORING HALF-CELL POTENTIAL (Malaysian Journal of Civil Engineering, 2018)
Corrosion of rebars in concrete is a key mechanism which determines the durability and service life of concrete structure. Half-cell potential of rebars in concrete subjected to a NaCl solution of 10% in the concentration has been monitored using embedded reference electrode in the concrete and computer operated automatic data acquisition system. A portable corrosion meter was also employed to measure half-cell potential and AC impedance. Initiation of corrosion in rebars were estimated by the former system and verified by the later. Corrosion initiation period was found to be from as early as 119 days and up to 360 days of chloride application depending on the characteristics of test specimens. Upon successful detection of corrosion initiation threshold chloride concentration for corrosion initiation was estimated. The estimated chloride threshold level for deformed rebar was found almost half of that with ideal plain steel rebar. Corrosion was spread over rebars depending on its surface characteristics.